2021
DOI: 10.1016/j.yexcr.2021.112594
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Maackia amurensis seed lectin (MASL) exerts pleiotropic actions on oral squamous cells with potential to inhibit SARS-CoV-2 infection and COVID-19 disease progression

Abstract: COVID-19 was declared an international public health emergency in January, and a pandemic in March of 2020. There are over 125 million confirmed COVID-19 cases that have caused over 2.7 million deaths worldwide as of March 2021. COVID-19 is caused by the SARS-CoV-2 virus. SARS-CoV-2 presents a surface “spike” protein that binds to the ACE2 receptor to infect host cells. In addition to the respiratory tract, SARS-Cov-2 can also infect cells of the oral mucosa, which also express the ACE2 receptor. The spike and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…MASL is an extremely abundant component in these extracts. MASL can survive digestion and has been found to inhibit viral infection, cancer, and inflammation, and arthritis progression [ 12 , 24 , [35] , [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…MASL is an extremely abundant component in these extracts. MASL can survive digestion and has been found to inhibit viral infection, cancer, and inflammation, and arthritis progression [ 12 , 24 , [35] , [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…Both plant lectins and griffithsin, the Man-specific lectin from the red alga Griffithsia sp., also inhibited the entry of SARS-CoV and MERS-CoV, respectively, in virus-infected cultured cells [42,74]. The Neu5Ac-specific Maackia amurensis lectin, MAL, inhibited the interaction of the SARS-CoV-2 S protein with the ACE2 receptor in cell cultures and decreased the expression of inflammatory mediators associated with COVID-19 disease progression [61].…”
Section: How Can the Infectivity Of Pathogenic Enveloped Viruses Be Affected By Lectins?mentioning
confidence: 96%
“…The effects of plant lectins on other pathogenic enveloped viruses have been more scarcely investigated. Plant lectins were identified as blocking agents for the entry of IV [45,52,57], HSV [57], HCMV [47,53,54], EBOV [47,48], LASV [47], and the coronaviruses MERS-CoV [51], SARS-CoV [42,51,54,62,63,104], and SARS-CoV-2 [50][51][52]58,60,61,66] in their corresponding host cells. However, depending on the viruses, the envelope glycoprotein(s) targeted by plant lectins are extremely diverse as mentioned in Table 2.…”
Section: How Can the Infectivity Of Pathogenic Enveloped Viruses Be Affected By Lectins?mentioning
confidence: 99%
“…Moreover, a previous study showed that SARS-CoV-2 could infect epithelial cells in situ and then shed into saliva which confirmed by scRNA-seq, orthogonal RNA, and protein expression analysis ( 83 ). Furthermore, it was demonstrated the inhibited expression of ACE2 and Furin through Maackia amurensis seed lectin (MASL) which has a potential therapeutic effect on COVID-19 by decreasing the expression of inflammatory mediators by oral epithelial cells ( 84 ). Considering of host response in SARS-CoV-2 infection, scRNA-seq and transcriptomic analysis were performed.…”
Section: Multi-omics Analysis Of Covid-19mentioning
confidence: 99%